Generation of pulsed proton beams in a vacuum diode with a passive anode; Vacuum; Vol. 216 - Pushkarev A. I. Aleksandr Ivanovich; Zhu Xiaopeng; Egorova Yu. I. Yulia Ivanovna; Polisadov S. S. Svyatoslav Sergeevich; Lei Ming Kai (2023, 2023)
Title screen